2021
DOI: 10.3390/antiox10081159
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Human Toxicology

Abstract: This Special Issue (same name as title) focuses on human exposure to foreign chemicals (xenobiotics) that cause oxidative stress [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…35 These small RNA molecules participate in various physiological processes, including development, immune response, and metabolism. 36 The expression of miRNAs can be influenced by cellular stress, including oxidative stress, 37 which is a significant mechanism in toxicology, 38 highlighting the relevance of miRNAs in toxicological processes. 39 Numerous studies have confirmed the involvement of miRNAs in regulating pesticide resistance in various pests.…”
Section: Discussionmentioning
confidence: 99%
“…35 These small RNA molecules participate in various physiological processes, including development, immune response, and metabolism. 36 The expression of miRNAs can be influenced by cellular stress, including oxidative stress, 37 which is a significant mechanism in toxicology, 38 highlighting the relevance of miRNAs in toxicological processes. 39 Numerous studies have confirmed the involvement of miRNAs in regulating pesticide resistance in various pests.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, clinical studies have observed markers of persistent endothelial dysfunction, such as impaired endothelial vasodilation, up to 24 h following a 1 h exposure to DEP [ 5 , 51 , 89 ]. Prolonged endothelial oxidative stress and dysfunction can have significant, adverse responses such as excessive pulmonary and systemic pro-inflammatory responses, thrombus formation, and the progression of atherosclerosis [ 14 , 36 , 38 ]. Therefore, inefficient endothelial intracellular stress resolution may be a key mechanism of how inhaled materials promote the development of respiratory and systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, practically all types of ROS, including free radical species and non-radical species, can induce the oxidative cleavage of proteins by glutamyl side chain oxidation or α-amidation pathways, leading to the generation of carbonyl groups on protein side chains. As we all know, the oxidation of lipids and proteins produces lipid peroxides and protein carbonyl groups, respectively, leading to the initiation of various tissue damages and aging related to oxidative stress, as well as involving the pathogenesis of many age-related degenerative diseases [ 24 , 26 ]. In the present study, we have found an increase on the serum levels of TBARS and protein carbonyl in aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggested that the activities of SOD and GSH-Px in the kidneys were significantly diminished during aging [ 37 ]. Fortunately, the decline in antioxidant defenses against oxidative stress during aging can be enhanced or maintained by supplementing extracellular antioxidants [ 26 ]. In addition, the green tea tannins could also help the residual kidneys to scavenge free radicals in rats with nephrectomy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%